Driver influence on vehicle track-ability on floating bridges - Balakrishna Bhat, Abhishek; Naik, Akshay; Adithya Reddy, Chintalapudi; Pishey, Kushaal; Manikanta, Venkatesh; Nishanth, Bharadwaj (My University, 2020)
Thinking from a traveler’s perspective, it can be said that it is important to reduce travel time. The Norwegian Public Roads Administration (NPRA) is working on a long term project to extend the coastal highway route E39 as a continuous stretch of road between Kristiansand and Trondheim. The road has a number of ferry crossings over fjords. Due to the depth in the fjords, it is not possible to build conventional bridges. Thus, the objective is to reduce the travel time by implementing a series of connections (e.g.submerged floating tunnels, subsea road tunnels and floating bridges). One such fjord crossing is the Bjørnafjorden bridge which spans for a length of over 5000 m. The floating bridge will be exposed to a number of varied weather conditions of different intensities. It is important to assess the vehicle handling and how the driver is experiencing the moving road surface in these conditions. The bachelor thesis which was proposed on the same topic, established a method to simulate the weather conditions in the CASTER driving simulator at Chalmers. The Automotive Engineering project (AEP) aims at evaluating the driving comfort and handling, when driving over the bridge in different weather conditions. The main approach adopted is to simulate the driving conditions in CASTER driving simulator, using the weather data provided by NPRA. Further, driving trials are conducted for a combination of different weather conditions and vehicle speeds for car and bus models. The results obtained from the trials are analyzed both subjectively using the driver feedback and objectively using the data obtained from the driving simulator, to make suitable conclusions and recommendations regarding the safe operating conditions of the bridge. The project further concludes the correlation between the weather conditions and drivability through both subjective and objective data analysis. The weather conditions were varied from no wind condition to a 100-year storm condition. Also, the most frequently occurring 1-year storm condition was studied in detail with only wind on the vehicle, sea swell and wind due to the wave conditions. A total of 157 driving trials were conducted with different vehicle speeds (70 kmph, 90 kmph and 110kmph) and different maneuvers like lane change and overtaking were performed to analyze the handling and stability of the car and bus. Straight line driving is also simulated to determine the operating conditions of bridge, to check the safe speed limit and ability of the driver to stay in lane. Another deliverable of the project is to develop a driver model to perform a greater number driving trials to test more conditions. Due to the lack of time and complexity of the weather data, a basic driver model has been developed and a thorough literature survey has been done to make suitable suggestions for the existing basic driver model as a future scope of the project. To sum it up, the vertical and lateral dynamics of the vehicles driving over the bridge are assessed in a virtual environment. A detailed analysis is done with the help of the data obtained in order to make suitable recommendations for safe driving on the bridge at different weather conditions.
Keywords: Floating bridge; Driving trials; Simulation; Driver comfort; Lane change; Overtake; Staying in lane; Driver model